Third national development plan,1975-80 - Federal Republic of Nigeria (Lagos : The Central Planning Office, Federal Ministry of Economic Development, 1980)
This contains the policies and programmes economic development plan of the Federal Republic of Nigeria for the year 1975-1980.
Nigeria Federal Ministry of Economic Development also known previously as Nigeria, Ministry of Economic Development and Establishments.
Revised volume II.
usc 18/10/2018
Ref
Keywords: Economic policy; Economic history; Social policy; Nigeria